Valgus Osteotomy of the Proximal Tibia in the Treatment of Arthritic Genu varo - Eduardo García Pérez; Luís Mena Aymé; Yovanny Ferrer Lozano; Pablo Oquendo Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Background: the assimilation of forces in a misaligned knee involves pain, deformity and decreased range of motion. Surgical correction delays the progression of degenerative joint affection and the performance of a total arthroplasty. Objective: To assess the results of valgus osteotomy of the proximal tibia in the treatment of arthritic genu varo. Methods: A descriptive study was conducted including 21 patients treated at the Orthopedics Service of the Julio Aristegui Villamil Teaching Territorial Hospital from January 2003 to September 2008, with the diagnosis of medial compartment knee osteoarthritis and angular deformity in the secondary rod. These patients underwent valgus osteotomy of the proximal tibia using an external fixator RALCA ®. Results: Male patients predominated (71.4%) with an average age of 56.3 ± 2.01 years old, as well as overweight as a predisposing factor (57, 1%) and 52.3% of grade II lesions according to Ahlback criteria . From the immediate postoperative period up to two years of evolution, we achieved an average femorotibial axis surgical correction of 9 ± 1.13 degrees, with a loss of correction of 2 ± 0.34 degrees. Wire osteitis was the most common complication (19, 04%). After two years of evolution the results were good in 80.9% of cases: partial or total arthroplasty of the knee was delayed, pain was reduced and functional capacities as well as life quality of patients were improved in 95, 2% of cases. Conclusions: Valgus osteotomy of the proximal tibia was effective in the treatment of arthritic genu varo.